Social inequality and democracy - Keh, Yi Ling (2017)
Existing studies have largely focused on the role of economic development in shaping democratic outcomes. In recent years, more attention has been placed on the effects of culture on democracy. A relatively unexplored cultural trait in the literature is the acceptance of social inequality. Using the Power Distance Index (PDI) as a proxy for the level of acceptance towards social inequality and the Freedom House Political Rights Index as a proxy for democracy levels, we construct a cross-sectional analysis to demonstrate the relationship between the level of acceptance towards social inequality and democracy levels. Our empirical results show that countries with a lower level of acceptance towards social inequality are more likely to experience higher democracy levels. This relationship holds even after we control for other determinants of democracy and introduce alternative measures of democracy. Using a long-difference analysis, we also verify the relevance of the level of acceptance towards social inequality in explaining the differences in the democracy levels of countries between two time periods. The key finding of our empirical analyses is that the level of acceptance towards social inequality is also another significant cultural predictor of democracy levels. Our results also shed light on how cultural forces can play an important role on the development of institutions.